A new approach for medial longitudinal arch estimation by "foot print": A comparative study - Vedi Neeraj; Dulloo Puja; Gandotra Achleshwar (Wolters Kluwer Medknow Publications, 2020)
Background: Medial longitudinal arch (MLA) is important as per the anatomical aspect of individual's foot. Its elastic properties reduce the risk of musculoskeletal wear and impairment. Various methods of its estimation have been presented by researchers. With this basis the aim of the study is to find the value of MLA by the devised mid-footprint planter angle method and compare it with the standard navicular height method. Methodology: Purposive analytical and comparative study done on 1st year health professional students of Sumandeep Vidyapeeth University (2015-2016 batch). MLA was estimated by the navicular height method and mid-footprint planter angle method on footprint after collecting their demographic and anthropometric data. The calculated values of MLA for both feet were compared by correlation coefficient by two different methods and Kruskal-Wallis test for the comparison as per body mass index (BMI) of participants. Results: Statistical significance was observed for right (−3.57 ± 0.85; P < 0.0001) and left (−6.4 ± 0.91; P < 0.0001) foot for MLA values by two methods, with higher level of Kappa agreement for right (0.755) and left (0.794) foot. Higher to middle level of correlation was observed for both the feet as per the two methods. Statistical significance as per gender was observed for left foot by navicular height method. While, no statistical significance was observed for MLA values as per BMI for both feet as per two methods. Conclusion: MLA values estimated by mid-footprint planter angle and compared by the standard navicular height method concludes that this method can be used in place of the gold standard in day-to-day basis, but extensive work needs to be done before considering it as a replacement, specifically in terms of sample size.